Young people with learning disabilities who sexually harm others: the role of criminal justice within a multi-agency response - Fyson, Rachel (Blackwell Publishing, 2007)
This paper outlines the key findings from a recent study of statutory service responses to young people with learning disabilities who show sexually inappropriate or abusive behaviours, with a particular focus on the involvement of criminal justice agencies. The study found that although inappropriate sexual behaviours were commonplace in special schools, and that serious acts of abuse including rape had sometimes occurred, education, welfare and criminal justice agencies struggled to work together effectively. In particular, staff often had difficulty in determining the point at which a sexually inappropriate behaviour warranted intervention. This problem was frequently compounded by a lack of appropriate therapeutic services. In many cases this meant that no intervention was made until the young person committed a sexual offence and the victim reported this to the police. As a consequence, young people with learning disabilities are being registered as sex offenders. The paper concludes by addressing some of the policy and practice implications of the study’s findings, particularly those which relate to criminal justice.